2009
DOI: 10.2343/geochemj.1.0016
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biomineralization of iron seepage water: Implication for the iron ores formation in intertidal zone of Zhoushan Archipelago, East China Sea

Abstract: The biogeochemcical reactions responsible for fossilized minerals preservation in ancient geological conditions are very often debatable, because little is known about the in situ processes at geo-historical period. In the present study, we describe the formation of iron ores collected in the intertidal zone of the Zhujiajian Island, Zhoushan Archipelago in the East China Sea. Morphological, mineralogical and geochemical analyses were performed on the iron ores and the surrounding geological materials. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Freshly formed amorphous biomineralization products can further transfer to more crystalline a-FeOOH. 40 Moreover, IOB can induce ferric hydroxide precipitation as a secondary by-product, and the ferric hydroxide may then serve as a precursor for more stable iron oxides, such as aFeOOH. 11 Some species belonging to the genus Acidovorax (such as Acidovorax sp.…”
Section: Corrosion Products and Bacterial Communitiesmentioning
confidence: 99%
“…Freshly formed amorphous biomineralization products can further transfer to more crystalline a-FeOOH. 40 Moreover, IOB can induce ferric hydroxide precipitation as a secondary by-product, and the ferric hydroxide may then serve as a precursor for more stable iron oxides, such as aFeOOH. 11 Some species belonging to the genus Acidovorax (such as Acidovorax sp.…”
Section: Corrosion Products and Bacterial Communitiesmentioning
confidence: 99%
“…Sheaths that have been shed will flocculate and settle. Iron precipitates attached to the sheath can then act as nucleation sites on which other precipitates can be deposited (Wu et al, 2009), either with more iron or with a carbonate crust in the case of Crystal Geyser. Heavily mineralized filaments may merge together in a mucilaginous mat upon flocculation, similar to the goethiteencrusted mats described by Hofmann & Farmer (2000).…”
Section: Iron Oxidementioning
confidence: 99%
“…Previous studies conducted by our group revealed that because of the fermentation of ancient woods, acidic pH (pH = 2.60), low oxygen content (DO = 2.19 mg/L), and reducing (Eh = -148.8 mV) seepage water significantly accelerated the release of Fe and Mn from bedrocks into the intertidal zone [ 33 ]. Fresh bacteriogenic oxides (BIOS) were present near the ancient wood layer characterized by very high contents of Fe (41.54%) and Mn (0.51%), which were 7–25 and 17–25.5 times higher than those of weathering bedrocks [ 33 35 ]. Iron-oxidizing bacteria, such as Leptothrix -like sheaths and Gallionella -like stalks, were abundant in BIOS, and played important roles in Fe biomineralization in the present study site [ 35 ].…”
Section: Introductionmentioning
confidence: 99%